Numerical analysis of the stability of abandoned cavities in bench blasting - Liu, K.; Hao, Hong; Li, X. (Pergamon, 2017)
When open-pit bench blasting approaches a site with underground cavities, concerns arise regarding the safe blasting distance to prevent collapse of the cavities because such collapses may induce other secondary problems related to the safety and workability of the site. It is therefore necessary to estimate the stability of underground cavities in the proximity of bench blasting. In this paper, blasting tests of small scale were carried out in a site with cavities and field blasting test data were measured to obtain the site-specific attenuation relations of PPV and principal frequency of stress waves. A numerical model is then developed based on these relations to calculate bench blasting induced stress wave propagation. The accuracy of the numerical prediction is verified by the field measured data. The verified numerical model is used to perform a series of simulations. The results are then used to assess the roof stability of cavities adjacent to upper bench blasting. Based on the numerical results, the response characteristics of cavity roof with respect to different explosive charge mass are also studied.